2011
DOI: 10.1007/s00405-011-1695-7
|View full text |Cite
|
Sign up to set email alerts
|

Glottic laser surgery: outcomes according to 2007 ELS classification

Abstract: The aim of the present investigation was to analyze the oncological results of a series of early stage glottic carcinomas treated with CO(2) laser-assisted endoscopic surgery. We focused on prognosis factors with significant impact on local control and disease-free survival (DFS). This retrospective study was conducted on a series of 177 consecutive patients with pT1-T2 glottic carcinomas treated with CO(2) laser-assisted endoscopic surgery in the period 2000-2007. All considered patients had at least a 24-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 29 publications
7
55
1
Order By: Relevance
“…In some studies, outcomes are outside the ranges shown above, in these cases mostly by a few percentage points. Larger variances are mainly seen in studies with <20 patients within a T categories, in which one single aberrant case will shift outcome significantly [3941]. Aside from random variations due to small numbers, positive deviances may also indicate selection bias with the most favorable lesions being chosen for TLM whereas the larger studies included in the table above tend to consist of (near) consecutive patients.…”
Section: Tlm: History Concepts/technique and Oncological Outcomementioning
confidence: 99%
“…In some studies, outcomes are outside the ranges shown above, in these cases mostly by a few percentage points. Larger variances are mainly seen in studies with <20 patients within a T categories, in which one single aberrant case will shift outcome significantly [3941]. Aside from random variations due to small numbers, positive deviances may also indicate selection bias with the most favorable lesions being chosen for TLM whereas the larger studies included in the table above tend to consist of (near) consecutive patients.…”
Section: Tlm: History Concepts/technique and Oncological Outcomementioning
confidence: 99%
“…Post biopsy, however, comparison of the patient data to the control group, revealed that some perceptual and acoustic changes had occurred, with some parameters no longer significantly different to the control group performance. As such, it may be suggested that these small shifts in function may be due to the removal of tumour tissue as supported by some authors [14][15][16].…”
Section: Discussionmentioning
confidence: 88%
“…In this study, where patients underwent several punch samples and multiple biopsy procedures, a deterioration to moderate-severe dysphonia was consistently demonstrated. These aforementioned authors and others go on to suggest that the excisional biopsy is the procedure of preference since the punch biopsy may be likely to harm the vocal cords and the excisional biopsy has the dual purpose of being both diagnostic and therapeutic in a single procedure [14,16,17,24]. Claims made by these studies, however, need to be interpreted with caution since specific voice and functional outcomes were not recorded nor rigorously investigated in their study designs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations